WAYS TO COUNTER CORRUPTION IN PUBLIC PROCUREMENT - О.S.Melnykov (Pressing Problems of Public Administration, 2016)
The meaning of corruption and corrupt actions are considered. The main corrupt practices in public procurement are identi ed and some measures to combat corruption in this area are offered.